2018
DOI: 10.1177/000313481808400229
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Predicts Morbidity after Colectomy for Ulcerative Colitis

Abstract: The rate of ulcerative colitis (UC), an inflammatory bowel disease, has been on the rise in the United States for the last several decades. Colectomy can be performed when other treatment options cannot provide a reasonable quality of life to patients with UC. Frailty has been shown to be a strong tool for evaluating preoperative risk factors for poor postoperative outcomes. The National Surgical Quality and Improvement Program cross-institutional database was used for this study. Data from 943 patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
0
24
1
1
Order By: Relevance
“…63 In a study specifically looking at postoperative outcomes after colectomy in UC, frailty was also associated with an increased odds of sepsis, cardiopulmonary complications, and overall morbidity (Table 2). 64 In a prior study, however, having at least 1 trait related to frailty was not found to be associated with major postoperative complications or length of stay after ileal pouch-anal anastomosis. 65 The differences may have resulted from the definitions of frailty used in each study.…”
Section: Frailtymentioning
confidence: 85%
“…63 In a study specifically looking at postoperative outcomes after colectomy in UC, frailty was also associated with an increased odds of sepsis, cardiopulmonary complications, and overall morbidity (Table 2). 64 In a prior study, however, having at least 1 trait related to frailty was not found to be associated with major postoperative complications or length of stay after ileal pouch-anal anastomosis. 65 The differences may have resulted from the definitions of frailty used in each study.…”
Section: Frailtymentioning
confidence: 85%
“…There is increasing interest in the concept of frailty. Various measures of frailty correlate with various outcomes, including postoperative morbidity and mortality, intensive care survival and postdischarge status . There is some evidence that specialist frailty assessment and treatment teams might alter outcomes .…”
Section: Alternative Scoring Systemsmentioning
confidence: 99%
“…In the same database, a study applying a frailty index validated in the database to a cohort of 943 patients who underwent a colectomy for UC, found that frailty was an independent and significant predictor of septic and cardiopulmonary complications, serious morbidity, re-operation, and overall mortality. 91 …”
Section: Frailty In Ibdmentioning
confidence: 99%